Search 79,284 tutors
FIND TUTORS
Ask a question
0 0

-4(2x+5)=2(-x-9)-4x

Tutors, please sign in to answer this question.

1 Answer

Original equation: -4(2x + 5) = 2(-x - 9) - 4x
 
 
First, distribute -4 into the parentheses on the left side while doing the same with 2 to the parenthesis on the right side to get: 
 
-8x - 20 = -2x - 18 - 4x
 
Second, you add like terms on each side to get: 
 
-8x - 20 = -6x - 18
 
Then, add like terms again, but this time leaving the variable x on the left side:
 
-2x = 2
 
Lastly, divide by -2 so that you're only left with the variable x on the left side:
 
Answer: x = -1